Space-time (dis)continuities in the linguistic landscape
1 online resource.
Keywords: "This collection spotlights the diachronic dimensions of the linguistic landscape, importance of exploring temporal dissonances in historical events in order to better understand semiotic, political, and social transformations across different communities over the last century. The volume seeks to expand the current borders of linguistic landscape research by situating the analysis of signs in the LL within their time-space organization, which has been understudied in existing scholarship. The book, featuring chapters from established and emerging scholars, argues that a focus on the historicity of the city text can reveal unique insights into the role of semiotic processes as precursors and support mechanisms for political and social changes. The collection is structured around different temporal clusters and geographic contexts across the globe where shorter and longer waves of politically-driven re-semioticization can be most sharply observed - post-colonial communities; post-communist societies; and recent and current socio-political upheavals. Taken together, the volume proposes a kaleidoscope view of the complex temporalities that underpin multimodal discourses in contested public spaces, offering new directions for linguistic landscape research. This book will be of interest to students and scholars in sociolinguistics, discourse analysis, semiotics, visual anthropology, and political science"--